A generating milling method for a spur face gear using a five-axis computer numerical control milling machine. (August 2016) - Wang, Yan-Zhong; Lan, Zhou; Hou, Liang-Wei; Zhao, Hong-Pu; Zhong, Yang
To improve the machining accuracy and production efficiency of face gears, this article presents a generating milling method for the spur face gear using a five-axis computer numerical control milling machine and proposes a milling principle of the spur face gear using a milling cutter. Based on the milling principle and theory of gearing, a mathematical model of the spur face gear milling cutter is established, and the design parameters of the cutter are determined. Considering the requirements of machine motion during the face gear milling process, a five-axis computer numerical control milling machine is developed to produce the face gear. Based on the structure of the milling machine, a mathematical model of the spur face gear is established, and a milling method is proposed. The spur face gear milling cutter is manufactured, and the face gear milling experiments are conducted on the self-developed milling machine. The measurement results of the tooth surface deviations indicate that the maximum deviation is 22.6 µm, and that the machined spur face gear accuracy can meet the requirements of roughing. The experimental results verify the validity of the proposed generating milling method and demonstrate that the generating milling method is an effective approach to improve the accuracy and efficiency of the spur face gear.